Advances in bridged 1,2,4-trioxane-based chemistry. A divergent approach to oxa-heterocycles based on ambident reactivity - Riveira, Martín Jorge (2010)
Heterogeneous catalytic hydrogenation of unsaturated 1,2,4-trioxanes derived from β-ionone-type dienones has been investigated. Our studies revealed a versatile reactivity of trioxanic substrates that led to the development of reaction methodology for the selective manipulation of the alkene and peroxide functionalities. Depending on the catalytic system used, divergent reaction pathways can be controlled to afford either the corresponding saturated 1,2,4-trioxanes or furan structures. A mechanistic rationalisation, which accounts for the reductive behaviour of these heterocycles, is proposed.